2016
DOI: 10.1002/ppsc.201500130
|View full text |Cite
|
Sign up to set email alerts
|

3D V3O7·H2O/Partially Exfoliated Carbon Nanotube Composites with Significantly Improved Lithium Storage Ability

Abstract: Currently, transition metal oxides are widely explored as electrode materials for lithium ion batteries due to their remarkably large reversible capacities. However, these materials always suffer from poor conductivities and slow lithium ion diffusion in the lattice. Given this, a distinctive 3D porous network is developed through partial exfoliation of multiwall carbon nanotubes, which can function as not only superior conductive additive but also as an efficient 3D porous scaffold. By self‐assembling with V3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…On the basis of previous studies, the morphologies and structures of the materials have a great influence on their electrochemical properties. Therefore, it is an effective and convenient route to improve the electrochemical performance of electrode materials through the development of novel architectures, which can shorten the access for ion diffusion and enhance the structural stability. , Many efforts have been made to obtain V 2 O 5 with different morphologies, such as nanobelts, nanowires, nanofibers, layer-by-layer V 2 O 5 quadrate structures, hierarchical spheres, porous octahedrons and hollow microspheres, etc., while few literature reports have focused on the comprehension among the properties of V 2 O 5 with different morphologies and discussed the effects of morphologies on the electrochemical properties. Qian et al reported the synthesis of V 2 O 5 nanowires, flower-like flakes, and curly bundled nanowires in the presence of polyethylene glycol 6000 (PEG), sodium dodecylbenzenesulfonate (SDBS), and Pluronic P-123 (P123).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous studies, the morphologies and structures of the materials have a great influence on their electrochemical properties. Therefore, it is an effective and convenient route to improve the electrochemical performance of electrode materials through the development of novel architectures, which can shorten the access for ion diffusion and enhance the structural stability. , Many efforts have been made to obtain V 2 O 5 with different morphologies, such as nanobelts, nanowires, nanofibers, layer-by-layer V 2 O 5 quadrate structures, hierarchical spheres, porous octahedrons and hollow microspheres, etc., while few literature reports have focused on the comprehension among the properties of V 2 O 5 with different morphologies and discussed the effects of morphologies on the electrochemical properties. Qian et al reported the synthesis of V 2 O 5 nanowires, flower-like flakes, and curly bundled nanowires in the presence of polyethylene glycol 6000 (PEG), sodium dodecylbenzenesulfonate (SDBS), and Pluronic P-123 (P123).…”
Section: Introductionmentioning
confidence: 99%
“…The ever-growing demand for high-energy and long-life Li-ion batteries (LIBs) for electrical vehicles, hybrid electrical vehicles, and other applications has prompted great research interest. To increase the energy density and cycling life of LIBs, it is more urgent to improve the discharge specific capacity and cycling performance of the cathode materials because the anode materials usually exhibit a higher capacity. , Among the various promising cathode candidates for LIBs, vanadium oxides (e.g., V 2 O 5 , VO 2 , V 6 O 13 , etc.) have attracted increasing research interest because of their distinct advantages of large discharge capacity, multiple vanadium oxidation states, abundance, and low cost. Recent reports have revealed that mixed-valence vanadium oxides, which exhibit larger discharge capacity and energy density, are more promising cathode materials. , Thus, another mixed-valence vanadium oxide, V 3 O 7 ·H 2 O, which was introduced by our recent review, has attracted our attention because it can deliver a strikingly large theoretical specific capacity of 379 mA h/g (corresponding to the 4 Li + intercalations), which is much larger than those of conventional LiMn 2 O 4 (148 mA h/g), LiCoO 2 (140 mA h/g), and LiFePO 4 (170 mA h/g) …”
Section: Introductionmentioning
confidence: 99%
“…Overall, the synthesis of 3D architectures of VO x (OH) y /CNT/rGO are attributed to the presence of CNT/rGO networks, and the interconnected structure will shorten the transmission path of electrons and ions, as well as boost the fast electron transfer and enhance the structural stability. This unique framework will facilitate the combination of VO x (OH) y and CNT/rGO, thus giving rise to satisfactory synergistic effects to improve their electrochemical performance. ,, …”
Section: Resultsmentioning
confidence: 99%
“…This unique framework will facilitate the combination of VO x (OH) y and CNT/rGO, thus giving rise to satisfactory synergistic effects to improve their electrochemical performance. 20,40,41 The specific surface area and porous properties of VO(OH) 2 , VO(OH) 2 /CNT, and VO x (OH) y /CNT/rGO were determined by N 2 adsorption/desorption measurements, as shown in Figure 2. Based on nitrogen isotherms (Figure 2a), the surface area calculated by BET equation and BJH pore volume of VO x (OH) y /CNT/rGO reach 24.6 m 2 •g −1 and 0.072 cm 3 •g −1 .…”
Section: Methodsmentioning
confidence: 99%